Sistem Penagihan Hutang Usaha Berbasis Web Pada PT Djojosindo Menggunakan Metode Extreme Programming - Chaerul Zaman; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT Djojosindo is a company engaged in digital printing. The provision of material goods for production is also ordered to vendors selected by the company on a tempo basis and can be referred to as trade payables. The process of recording all accounts payable data obtained from several invoices received from vendors is done manually in a ledger so that it is less effective in terms of searching for data and calculating accounts payable which needs to be known in nominal terms, especially debts that must be paid in a timely manner. a long time and can make the company's expenses unstable and not timely causing invoice data to be missed which has an impact on late invoice payments. Payment of accounts payable is done manually referring to the due date of each invoice, making invoice payments sometimes exceed the due date which can affect the company's reputation in the eyes of the vendor and reduce the vendor's level of trust in the company.The process design method is focused on model development using UML (Unified Model Language) and using the PHP programming language, as well as Xampp v3.2.2 with Apache as the web server and MySQL as database storage.This research produces an application that is able to record all accounts payable data so that it is easy to find data and estimate future debt calculations in the future so as to reduce the impact of missed invoice recordings that often occur by employees and this application is able to make invoice payments automatically by the system to customers. vendor accounts according to the payment due date.